Apakah Investasi pada Industri Pulp and Paper adalah Pilihan yang Tepat ? - Kori Nofianti; Yurniwati Yurniwati; Defriko Gusma Putra (Universitas Negeri Padang, 2022)
Investment is an economic activity that has the hope of prosperity in the future. The development of investment in financial instruments is increasing due to availability and demand. The Pulp and Paper industry in Indonesia currently has the potential to grow. Financial statement analysis is used to help decision makers. The type of research used in this research is quantitative research. by using secondary data obtained from the Annual Report obtained from the IDX website and the website of the company being sampled. The population in this study is the Pulp and Paper Industry which is listed on the Indonesia Stock Exchange in the financial statements for the period 2013 to 2017. The sample in this study is 5 companies consisting of: PT. Indah Kiat Pulp and Paper, Tbk (INKP), PT. Toba Pulp Lestari, Tbk (INRU), PT. Paper Basuki Rachmat Indonesia, Tbk (KBRI), PT. Alkindo Naratama, Tbk (ALDO) and PT. Fajar Surya Wisesa, Tbk (FASW). The results of the study recommend investors to choose the Pulp and Paper industry, because it has the potential to grow and develop. This is supported by campaigns and movements to reduce the use of single-use products, which of course can directly affect the demand for paper needs in the future and will automatically increase and increase paper prices.